Effect of aerodynamic force change caused by car-body rolling on train overturning safety under strong wind conditions. Issue 2 (1st February 2022) - Liu, Dongrun; Tomasini, Gisella Marita; Cheli, Federico; Zhong, Mu; Zhang, Lei; Lu, Zhaijun
Abstract : Understanding the relationship between car-body vibration and train aerodynamic forces is very important for developing a reasonable operation plan when the train passes through the complex terrain under strong wind conditions. In this study, car-body vibration under strong wind conditions was initially investigated with a full-scale test. Then the train aerodynamic forces for different rotation configurations with a train speed of 250 km/h and a wind speed of 25 m/s were further studied using a Computational Fluid Dynamics simulation. The results revealed that the car-body vibration was primarily a low-frequency and large-amplitude rolling and transverse coupling motion in windy conditions, and the roll angle of the car-body with respect to the bogie frame was greater than that of the bogie frame with respect to the track. The train aerodynamic force coefficients are sensitive to the car-body rolling motion in windy conditions. When the car-body rolling from the windward side to the leeward side, the significant reduction in the negative pressure at the bottom of the car-body was the dominant reason for the train lift force increase, and the effect of the aerodynamic force change caused by car-body rolling on the train overturning risk was not significant.